Demographic, employment, and wage trends in South Africa - Haroon Bhorat; Karmen Naidoo; Morné Oosthuizen; Kavisha Pillay (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper looks to uncover the growth traps and opportunities for the South African economy, with a focus on underlying labour market dynamics. We explore the potential of South Africa's demographic dividend. We also consider the structure of the labour market and the growth-employment interactions, which uncover the skills-biased labour demand path of the economy and a rising trend in the use of labour brokers to source temporary workers. Finally, we show a new labour market trend has emerged: a rise in the share of public sector employment along with higher conditional returns to public sector workers than to those in the private sector.
Keywords: J11; J20; J45; L33; 330; South Africa; economic growth trap; labour market dynamics; skills-biased labour demand; demographic dividend